Joint engagement and early language abilities in young children with Down syndrome - Mattie, Laura J.; Fanta, Daniela (Frontiers in Psychology, 2023)
Early social strengths likely serve as a foundation for language acquisition for young children with Down syndrome (DS). One way to characterize early social skills is to examine a child’s engagement with a caregiver around an object of interest. The current study examines joint engagement in young children with DS and its relation to language abilities at two-time points in early development. Participants were 16 young children with DS and their mothers. At two time points, mother-child free plays were completed and coded for joint engagement. Language abilities were measured at both time points using the Vineland Adaptive Behavior Scales 3rd edition and the number of words understood and produced on the MacArthur-Bates Communication Development Inventory. Young children with DS spent more time in supported joint engagement than coordinated joint engagement at both time points. Using a weighted joint engagement variable, children with DS who had higher weighted joint engagement had lower expressive language raw scores on the Vineland when controlling for age at Time 1. At Time 2, children with DS who had higher weighted joint engagement had higher expressive and receptive language raw scores on the Vineland when controlling for age. Predictively, children with DS who had a higher weighted joint engagement at Time 1 had a lower number of words produced at Time 2 when controlling for l age at Time 1. Our results suggest that young children with DS may compensate for their difficulties with language by using joint engagement. These results highlight the importance of teaching parents to be responsive during interactions with their child to move them into both supported and coordinated engagement, which in turn may foster language development.